PROGRAM "GIVING BACK TO THE COMMUNITY" DI DESA WISATA CEPAKA OLEH MINOR PROGRAM NHL STENDEN UNIVERSITY BELANDA DAN UNIVERSITAS TRIATMA MULYA BALI - Karta, Ni Luh Putu Agustini; Wiles, Erna Zulaini; Wardani, Rani Kusumo; Irwanti, Ni Ketut Dewi; Jong, Mark De (Jurnal Abdi Insani, 2023)
Giving Back To The Community (GBTTC) is the implementation of the Ministry of Education and Culture's Independent Learning Campus (MBKM) program. This activity was carried out by students of the Dutch NHL Stenden University of Applied Science (NHL Stenden) minor program in collaboration with students of Triatma Mulya University (UNTRIM) Bali. This activity aims to share knowledge by teaching school children at Balai Banjar (RW) and implementing the theory of laughter yoga and meditation for the ELDERLY. The method of this activity is: carried out by student groups consisting of the NHL Stenden and UNTRIM teams, where each group teaches children and teaches the elderly in four balai banjar (RW) in turn. Each team consists of students taking the minor Entrepreneurship and Business Consultant (EBC) programs, Event Management (EM) and Mindfullness Leadership (ML). Students of the EBC and EM minor programs teach school children in balai banjar (RW), students of the ML minor program teach laughter yoga, and elderly gymnastics. All Stenden NHL students and UNTRIM students also had the opportunity to enjoy the tourism village program that was packaged with UNTRIM students. The results of this project show that; the usefulness of the interaction between foreign students and the local community in the context of learning for school children has a positive impact on developing their international outlook. Cultural learning, social interaction with foreigners, has a positive impact on improving the quality of life for the ELDERLY. Simultaneously teaching and sharing activities with the ELDERLY in the village by NHL Stenden students and UNTRIM students contributed reciprocally to both parties.